Development of Ergonomics Checklist on Stroke Therapy Aids (Wearable Elbow Exoskeleton) - Novie Susanto; Christ Novia Saraswati; Wiwik Budiawan; Rifky Ismail (Center for Biomechanics, Biomaterials, Biomechantronics and Biosignal Processing (CBOIM3S), 2022)
This study aims at building a checklist used for each stage of wearable Elbow Exoskeletons development. The Wearable Elbow Exoskeleton is one of the handstroke therapy aids which was developed by Diponegoro University. The product is still in the form of a prototype so some tests must be carried out before the product is tested on respondents. The test so far is still focused on functionality tests. This study provides a general checklist for ergonomics testing of stroke therapy aid products. The method of the checklist is developed based on an exploratory study and literature review for producing appropriate tests related to product characteristics. There are three iterations of product development and each version repairs the previous version. The implementation of the checklist shows that on the third iteration, the product is aligned with the objective of development and reaches the targeted level of respondents’ satisfaction.